RETRACTED: The necessity of developing mobile applications for people with disabilities - Farmanov Erkin; Radjabov Odil; Davronov Istamkhuja; Yuldashev Kamol; Sharipov Bekzod; Ibragimov Nutfillo (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 138, 00001 (2024), https://doi.org/10.1051/bioconf/202413800001